Breast Awareness, Self-Reported Abnormalities, and Breast Cancer in Rural Ethiopia: A Survey of 7, 573 Women and Predictions of the National Burden. (19th March 2021) - Ayele, Wondimu; Addissie, Adamu; Wienke, Andreas; Unverzagt, Susanne; Jemal, Ahmedin; Taylor, Lesley; Kantelhardt, Eva J.
Abstract : Background: Breast cancer (BC) is the most frequently diagnosed cancer and leading cause of cancer deaths among women in low-income countries. Ethiopia does not have a national BC screening program, and over 80% of patients are diagnosed with advanced stage disease. The aim of this study was to assess how many women self-report a breast abnormality and to determine their diagnoses in rural Ethiopia. Methods: A community-based cross-sectional study was conducted among 7, 573 adult women. Women were interviewed and educated about breast awareness, and those who reported breast abnormalities underwent clinical examination by experienced surgeons. Ultrasound-guided fine needle aspiration cytology (FNAC) was obtained, and cytological analysis was performed. The findings were projected to the female population of Ethiopia to estimate current and future burden of diseases. Findings: Of the 7, 573 women surveyed, 258 (3.4%) reported a breast abnormality, 246 (3.2%) received a physical examination, and 49 (0.6%) were found to be eligible for ultrasound-guided FNAC or nipple discharge evaluation. Of all the cases, five (10.2%) breast malignancies were diagnosed. We projected for Ethiopia that, approximately, 1 million women could self-report a breast abnormality, 200, 000 women could have a palpable breast mass, and 28, 000 women could have BC in the country. Conclusion : The health care system needs to build capacity to assess and diagnose breast diseases in rural areas of Ethiopia. These data can be used for resource allocation to meet immediate health care needs and to promote detecting and treating BC at earlier stages of disease. Implications for Practice: Routine mammography screening in a resource-limited country with a young population is neither sensitive nor affordable. Clinical breast examination with consecutive ultrasound-guided fine needle aspiration cytology may ensure early diagnosis, downstage disease, and reduce breast cancer mortality. This study had the unique opportunity to educate over 7, 573 rural women about breast abnormalities and offer clinical and cytological diagnosis for reported breast abnormalities. The findings were extrapolated to show the nationwide burden of breast abnormalities and unmet diagnostic needs. These data will serve as policy guide to improve adequate referral mechanisms and breast diagnostic and treatment facilities. Abstract : Developing tailored interventions for the prevention of breast cancer in Ethiopia is a major challenge in this resource-limited country. This article reports on the proportion of adult women with self-reported breast abnormalities in a rural region of Ethiopia, assessing the diagnosis of these abnormalities and extrapolating the disease burden for the entire Ethiopian female population.